Efficacy of Jinshui Liujun decoction on chronic obstructive pulmonary disease patients: a systematic review and meta-analysis - Huang, Wanqiu; Wang, Hui; Wu, Di; Zhang, Lu; Tong, Jiabing; Yu, Minghui; Li, Zegeng; Yang, Qinjun (Frontiers in Pharmacology, 2025)
BackgroundJin Shui Liu Jun Decoction (JLD) is a classical prescription in Traditional Chinese Medicine (TCM). In recent years, JLD has shown beneficial effects on patients with chronic obstructive pulmonary disease (COPD). However, the existing clinical research results are contradictory, and high-quality, evidence-based medical evidence is lacking. Therefore, the exact therapeutic efficacy of JLD has not been fully evaluated.ObjectivesThis study aimed to ascertain the precise therapeutic efficacy of JLD in treating COPD.Data sources and MethodA search of 10 electronic databases was conducted up to 30 November 2024. The standardized mean difference (SMD) was used to assess continuous variables, while the relative risk (RR) was calculated to evaluate dichotomous variables. The Luis Furuya-Kanamori (LFK) asymmetry index, along with the Doi plot, Egger’s test, and Begg’s test, were used to assess publication bias. Sensitivity analysis was performed to evaluate the stability of the conclusions. Furthermore, trial sequential analysis (TSA) was used to assess the risk of false-positive results and to estimate the required sample size for the meta-analysis. Finally, single-factor and multi-factor meta-regression were conducted to analyze the sources of heterogeneity.ResultsA total of 22 trials meeting the inclusion criteria were included, including 1,817 COPD participants. The meta-analysis indicated that JLD could improve overall treatment efficacy (RR = 1.15, 95% CI: 1.053–1.256, PZ = 0.002) and pulmonary function (FEV1: SMD = 0.661, 95% CI: 0.276–1.046, PZ = 0.001; FEV1% Predicted: SMD = 0.368, 95% CI: 0.067–0.669, PZ = 0.017; FVC: SMD = 0.814, 95% CI: 0.392–1.235, PZ < 0.001; FEV1/FVC Ratio: SMD = 0.602, 95% CI: 0.311–0.893, PZ < 0.001) in COPD, potentially offering benefits in traditional Chinese medicine syndrome scores (SMD = 0.936, 95% CI: 0.301–1.571, PZ = 0.004) and 6-min walk distance (6MWD: SMD = 0.744, 95% CI: 0.182–1.306, PZ = 0.009). The subgroup analysis revealed a higher overall efficacy and improvement in FEV1/FVC Ratio of JLD treatment for stable chronic obstructive pulmonary disease (sCOPD) compared to the acute exacerbation of chronic obstructive pulmonary disease (AECOPD) group (SMD:0.605 v.s. 0.574, PZ < 0.05). Additionally, compared to the simple JLD treatment plan, the conventional biomedicine (CBM)+JLD scheme showed superior overall efficacy in treating COPD patients (RR = 1.15, 95% CI: 1.043–1.268, PZ = 0.005).ConclusionTreatment with JLD can effectively improve the overall efficacy and pulmonary function (FEV1%pred requires more research for confirmation) of COPD patients. However, the methodological quality of the included trials may limit the generalizability of the study’s findings. Sources of heterogeneity were partially identified through meta-regression, but further rigorous randomized controlled trials are still required.Systematic Review Registrationhttps://osf.io/msw7b.